2011
DOI: 10.1159/000327979
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on Facial Emotion Recognition Capacity in Beginning Alzheimer’s Disease

Abstract: Objective: It was the aim of this study to investigate facial emotion recognition (FER) in the elderly with cognitive impairment. Method: Twelve patients with Alzheimer’s disease (AD) and 12 healthy control subjects were asked to name dynamic or static pictures of basic facial emotions using the Multimodal Emotion Recognition Test and to assess the degree of their difficulty in the recognition task, while their electrodermal conductance was registered as an unconscious processing measure. Results: AD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 99 publications
0
18
1
Order By: Relevance
“…Compared with mood disorders patients and healthy older adults, AD patients tend to select happy but not negative labels in emotion recognition tasks [66]. Consistently, Wiechetek and his colleagues [67] also found that AD patients preserved the recognitions of happy but not fear or disgust faces. By adopting a sophisticated matching task, a recent study [68] showed that only the abilities to recognize happy but not sad or angry faces were relatively preserved among early AD patients.…”
Section: Positivity Bias On Early Ad's Emotional Perceptionmentioning
confidence: 66%
“…Compared with mood disorders patients and healthy older adults, AD patients tend to select happy but not negative labels in emotion recognition tasks [66]. Consistently, Wiechetek and his colleagues [67] also found that AD patients preserved the recognitions of happy but not fear or disgust faces. By adopting a sophisticated matching task, a recent study [68] showed that only the abilities to recognize happy but not sad or angry faces were relatively preserved among early AD patients.…”
Section: Positivity Bias On Early Ad's Emotional Perceptionmentioning
confidence: 66%
“…Diagnosis of possible or probable Alzheimer’s disease in seventeen studies were made according to criteria of the National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimers Disease and Related Disorders Association (NINCDS/ADRDA) [ 4 , 12 , 13 , 15 17 , 19 , 21 , 23 , 25 , 27 , 28 , 31 , 33 , 35 , 38 , 39 ], or based on the DMS-IV TR criteria [ 18 , 22 , 24 , 31 ]. Other studies also used biomarkers [ 14 ] or a geriatric evaluation [ 18 ] and in one study the specific criteria used to isolate possible or probable AD were unclear [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Control participants included informal caregivers of the AD patients [ 15 , 25 , 26 ], spouses [ 25 ], other relatives [ 4 , 39 ], community-based healthy elderly [ 4 , 15 , 16 , 17 , 19 , 24 , 25 , 29 , 30 , 35 , 38 , 39 ], non-demented patients from (neurological) hospitals [ 13 , 22 , 34 , 37 ], outpatient clinics [ 22 , 23 ], research centres [ 36 ], paid volunteers [ 20 ] or residents of a long-term care facility [ 12 , 33 ]. In some studies the control group was not specified [ 14 , 18 , 21 , 27 , 28 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While decreased recognition of static emotions has often been reported in AD patients [1517], these studies either did not control for patients’ general cognitive impairment [17], or reported that emotion labeling was predicted by executive functions (EF) and MMSE scores [16]. Variable results in such studies over the past decade suggest that AD patients’ failure on tests measuring facial emotion identification may often reflect general cognitive or perceptual impairment rather than a focal emotion processing deficit.…”
Section: Perception Of Social and Emotional Signalsmentioning
confidence: 99%